Genomics, obesity and the struggle over responsibilities - Korthals, Michiel (International library of environmental, agricultural and food ethics, 2011)
This volume addresses the overlapping aspects of the fields of genomics, obesity and (food) ethics. It is unique in its examination of the implications of genomics for obesity from an ethical perspective. Genomics covers the sciences and technologies involved in the pathways that DNA takes until the organism is completely built and sustained: the range of genes (DNA), transcriptor factors, enhancers, promoters, RNA (copy of DNA), proteins, metabolism of cell, cellular interactions, organisms. Genomics offers a holistic approach, which, when applied to obesity, can have surprising and disturbing implications for the existing networks tackling this phenomenon and for fundamental ethical notions, strategies and practices. In the book several strategies to match genomics, obesity, society and ethics are studied, and a happy match is proposed based on a pragmatist ethical framework. The ethical framework presented is inspired by the interaction between a procedural perspective emphasizing the necessity of consultative and participatory organizational relationships in the new interfaces between (nutri)genomics, medicine and food, and a substantive perspective that both cherishes individual autonomy and embeds it in socio-cultural contexts.